A new biased estimator in logistic regression model. Issue 2 (3rd March 2016) - Özkale, M. Revan; Arıcan, Engin
Abstract : In this paper, the r − k class logistic estimator which combines the ridge logistic and principal components logistic regression (PCLR) estimators is proposed. The comparisons of the r − k class logistic, ridge logistic and PCLR estimators to the maximum likelihood (ML) estimator according to the asymptotic matrix mean square error (MSE) criterion and the comparisons of the r − k class logistic estimator to the ML, PCLR and ridge logistic estimators in the sense of asymptotic scalar MSE criterion are done. The results are illustrated with numerical examples and a simulation study is done.